2004
DOI: 10.1128/jcm.42.10.4615-4619.2004
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Antibodies against Noroviruses among Students in a Chinese Military Medical University

Abstract: Noroviruses (NVs) are important causes of nonbacterial gastroenteritis in humans, but the role of NVs as a cause of diseases in the Chinese people, particularly in Chinese military personnel, remains unclear. This study investigated antibody prevalence and factors that associate with the prevalence of antibody to NVs among students attending a military medical university. Serum specimens were tested by an enzyme-linked immunosorbent assay for immunoglobulin G antibody to recombinant capsid antigens of three NV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…63,64 NoV infections occur worldwide and although some studies demonstrated a greater prevalence and younger age of acquisition of antibody among children in developing countries compared with those in industrialized countries, these differences were not consistently observed. 65 Infections with genogroup II NoVs occur more commonly than those with genogroup I NoVs.…”
Section: Antibody Prevalencementioning
confidence: 81%
“…63,64 NoV infections occur worldwide and although some studies demonstrated a greater prevalence and younger age of acquisition of antibody among children in developing countries compared with those in industrialized countries, these differences were not consistently observed. 65 Infections with genogroup II NoVs occur more commonly than those with genogroup I NoVs.…”
Section: Antibody Prevalencementioning
confidence: 81%
“…A number of factors are known to play a role in the increased prevalence of some infectious diseases in developing countries. These include poor hygiene and sanitation, less access to healthcare, overcrowding as well as socio-cultural differences wherein people in India live in larger family units when compared to developed countries [25][28]. Norovirus infections, similar to rotavirus infections, are endemic in infants and children.…”
Section: Resultsmentioning
confidence: 99%
“…Eight receptor-binding patterns have been described (Table 1) ( Refs 51,52,53,54,61). The association of NV infection with HBGA types has also been demonstrated by outbreak investigations and antibody prevalence against certain types of NVs ( Refs 62,63,64,65,66). In addition, the HBGAs in human milk were also found to block NVs from binding to their receptors ( Refs 67,68,69,70), suggesting that the milk HBGAs could serve as a potential decoy receptor in the Polymorphism of the human HBGA system…”
Section: Molecular Approaches For Studying Nv-host Interactionmentioning
confidence: 92%